The problem of the ultraviolet catastrophe - Silva , Jizreel Pereira da; Souza , Brenda Ramos; Araújo , Robson do Carmo (International Journal of Scientific World, 2025)
The study of thermal radiation emitted by a black body founded the quantum theory of radiation. The development of this study revealed ‎discrepancies with the predictions of classical physics, especially the failure of the Rayleigh-Jeans Law for short wave-lengths, known as the ‎ultraviolet catastrophe. Within this context, Max Planck suggested that the energy emitted by these bodies be quantized in multiples of ‎ ‎, ‎which we know as Planck's constant, developing Planck's Law, which accurately describes the behavior of the blackbody radiation spectrum, intertwining his theory with experimental results. From this, it was possible to prove the limi-tation of classical physics to explain some ‎phenomena, thus establishing a cradle for quantum physics. This paper addresses these findings and their implications for understanding ‎thermal radiation by analyzing the evolution of the study of blackbody radiation and comparing the different equations proposed over time‎.